2014
DOI: 10.1007/s10517-014-2581-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuropeptide Y in Myocardial Contractility of Rats during Early Postnatal Ontogeny

Abstract: We studied the effect of neuropeptide Y in concentrations of 10(-10)-10(-6) M on myocardial contractility of rats at the age of 7, 21, and 100 days. Studying the isometric contraction of myocardial strips showed that neuropeptide Y decreases the force of myocardial contraction in 7-day-old rat pups. Exogenous neuropeptide Y produced a biphasic effect in 21-day-old rats, which was manifested in the increase and subsequent decrease in myocardial contractility. Neuropeptide Y had little effect on myocardial contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…On the other hand, in the Langendorff procedure, we used 12-week-old mice and revealed that NPY showed neither positive nor negative inotropic and chronotropic effects. This result is in agreement with the findings of Zverev et al (2014) . In general SC occurred in adults and is uncommon in juveniles.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, in the Langendorff procedure, we used 12-week-old mice and revealed that NPY showed neither positive nor negative inotropic and chronotropic effects. This result is in agreement with the findings of Zverev et al (2014) . In general SC occurred in adults and is uncommon in juveniles.…”
Section: Discussionsupporting
confidence: 94%
“…NPY had little effect on the myocardium of 100-day-old rats. The reaction of the myocardium to NPY appears to differ with age ( Zverev et al, 2014 ). The study examined the reaction of the myocardium after stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that NPY can suppress myocardial contractility by inhibiting the energy metabolism of mitochondria in the cardiomyocytes. [ 20 21 ] Therefore, it is reasonable to propose that the upright plasma NPY may take part in the decline of CO in the positive-response period during the HUT by suppressing myocardial contractility. As mentioned above, the increase in the TPVR and the decline in CO are characteristic responses in children with VVS during the HUT.…”
Section: Discussionmentioning
confidence: 99%